2018
DOI: 10.17294/2330-0698.1628
|View full text |Cite
|
Sign up to set email alerts
|

Problems Experienced in the Second and Third Months After Discharge From a Heart Failure-Related Hospitalization

Abstract: Part of the Cardiology Commons, Cardiovascular Diseases Commons, Dietetics and Clinical Nutrition Commons, and the Other Nursing Commons Recommended Citation Recommended Citation Grant JS, Graven, LJ. Problems experienced in the second and third months after discharge from a heart failure-related hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…117 Research is needed to examine coping strategies over the trajectory of HF as self-care demands and resources change and novel situations emerge. 118 Environmental Factors That Influence Heart Failure Self-care This update to the theory includes important new content summarizing environmental influences on HF selfcare. McCauley and Hayes 119 organize environmental science into 4 main categories: physical (eg, natural disasters), chemical (eg, allergens, lead exposure, and air pollution), biological (eg, antibiotic resistance), and cultural or social hazards (eg, violence, racism).…”
Section: Person Factors That Influence Heart Failure Self-carementioning
confidence: 99%
See 2 more Smart Citations
“…117 Research is needed to examine coping strategies over the trajectory of HF as self-care demands and resources change and novel situations emerge. 118 Environmental Factors That Influence Heart Failure Self-care This update to the theory includes important new content summarizing environmental influences on HF selfcare. McCauley and Hayes 119 organize environmental science into 4 main categories: physical (eg, natural disasters), chemical (eg, allergens, lead exposure, and air pollution), biological (eg, antibiotic resistance), and cultural or social hazards (eg, violence, racism).…”
Section: Person Factors That Influence Heart Failure Self-carementioning
confidence: 99%
“… 117 Research is needed to examine coping strategies over the trajectory of HF as self-care demands and resources change and novel situations emerge. 118 …”
Section: Problem Person and Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Following up a previous publication, 19 Grant and Graven add to this theme issue with a mixed-methods study of patient experiences in months 2 and 3 following hospitalization for HF. 20 Managing treatment and HF symptoms were the most common problems identified during this time period. Barriers such as negative emotions/moods, difficulty coping, and inadequate resources also were identified.…”
Section: T His Spring In Volume 5 Issue 2 Of the Journal Of Patientmentioning
confidence: 93%
“…Harkening back to the complexity inherent to shared decision-making caused by uncertainty and competing priorities, the authors noted HF patients expressed uncertainty about the future and even "hopeful" uncertainty about their diagnosis. 20 Their findings also suggested that competing, but interrelated, problems like financial insecurity impacted HF self-management. Family-based interventions were suggested for improved self-care.…”
Section: T His Spring In Volume 5 Issue 2 Of the Journal Of Patientmentioning
confidence: 97%